Delia Salter Bacon papers - Bacon, Delia Salter, 1811-1859.
Correspondence (1856-1857) between Bacon and Nathaniel Hawthorne and others on the subject of the Shakespeare-Francis Bacon controversy. Includes later letters from Julius Goodman and Norman Holmes Pearson to Charles E. Feinberg concerning Delia Bacon.
Transcripts of originals in the Folger Shakespeare Library.
Author.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Bacon, Francis, -- 1561-1626 -- Correspondence; Feinberg, Charles E., -- 1899-1988 -- Correspondence; Goodman, Julius -- Correspondence; Hawthorne, Nathaniel, -- 1804-1864 -- Correspondence; Pearson, Norman Holmes, -- 1909-1976 -- Correspondence; Shakespeare, William, -- 1564-1616.; Literature; Authors